Dampak Sentralisasi PT Satya Mitra Waspada terhadap Sikap Kerja, Keterampilan Kerja, Produktivitas Kerja Karyawan PT SATYA MITRA WASPADA : Analisa SWOT. - farhan, muhammad (Lembaga Pengabdian Masyarakat, 2025)
This study analyzes the changes that have occurred in the institution of the Faculty of Economics, Krisnadwipayana University as a result of the centralization of the institution. The author uses SWOT analysis tools to conduct this research. The author used the interview method to collect information at the PT Satya Mitra Waspada. The results of this study are the advantages and disadvantages of the impact of Institutional Centralization.